Pengabdian kepada masyarakat melalui lanskap linguistik model kampung literasi agrowisata Desa Tapak Gedung Kabupaten Kepahiang - Arono, Arono; Diani, Irma; Yunita, Wisma; Supriyadi, Rendi; Guntur, Rahmat (IKIP SILIWANGI, 2025)
Local cultural literacy with character is currently lacking a place in society. The language used does not describe and reflect the area in which an area is located. This service aims to describe and disclose community data on the linguistic landscape and the tendency to read and write in the community, train the community in reading and writing in the community so that they can foster interest in reading and writing, compile literacy into an agro-tourism-based book both print and through online media, as well as describe responses to reflections on activities that have been carried out to provide input and action on literacy village model activities that have been carried out. The service model that is carried out is the APTE Model (Needs Analysis, Training, Action, and Evaluation). The results of the service carried out, namely the people's reading and writing interest is good but still lacking in availability and sales activity. Likewise, with illiteracy, only 9.6% of those who are still illiterate also occur in older people. The linguistic landscape that the research team found in Tapak Gedung Village is generally found in public spaces both outside and inside buildings. The linguistic landscape generally concerns the nameplate of a building (school name, office name, mosque name, name, signage in the form of advertisements and posters (health, hygiene, environmental advertisements), and activity announcements or activity banners. APTE Model (Needs Analysis, Training) , Action, and Evaluation) can foster interest in reading and writing in the Tapak Gedung community. The output of this training is agro-tourism literacy that is produced which is called online/website and print. Based on this community service activity, this activity is very well done so that it has an impact on increasing reading and writing culture of the linguistic landscape of the Tapak Gedung community with the presence of Tabatage Unib.